Self-medication practices among health care professionals in a Private University, Malaysia (International Current Pharmaceutical Journal, 2012)
The purpose of this study was to evaluate and analyze the prevalence of self-medication practice among healthcare professionals in a private university, Malaysia. Prospective, quantitative, cross-sectional design which attempts to measure the self-medication practices among the teaching healthcare personnel through questionnaire survey form, self-developed and pre-validated consisting of open and closed-ended questions. Among respondents, 77.6% were practicing self medication. The reasons were, familiar with treatment options (23.5%) and mild illness (20%) and the highest practicing respondents were 30-39 years (76.3%). The reason among those who did not practice self- medication was risk of adverse reactions (31.6%). Self-medication practice was more prevalent among medical professionals (86.5%) followed by pharmacy and dentistry (70%). Headache (15.7%), cough and cold (15%) among illness and analgesics (13.1%) and antipyretic (12.7%) among drugs induced most respondents to practice self- medication. This study reveals very high prevalence of self-medication practice among healthcare professionals in the local private university. Exposure to drugs, knowledge of their illness and treatment choice remains main contribu- tors. The healthcare professionals must be encouraged to enter the patient role.DOI: http://dx.doi.org/10.3329/icpj.v1i10.11846 International Current Pharmaceutical Journal 2012, 1(10): 302-310